Determinants of Absorptive Capacity: a systematic literature review - Silveira, Naijela Janaina Costa; Ferraz, Diogo; Mello, Diego Scarpa de; Polloni-Silva, Eduardo; Rebelatto, Daisy Aparecida do Nascimento; Moralles, Herick Fernando (Revista Gestão da Produção Operações e Sistemas, 2021)
Purpose – To conduct a literature review on the determinants of Absorptive Capacity (AC), which allows for productivity spillovers from Foreign Direct Investment (FDI) in developed and developing countries. Theoretical framework – This study is based on the literature indicating that before benefiting from spillovers, companies need a certain level of knowledge and expertise. Design/methodology/approach – A Systematic Literature Review (SLR) of empirical studies on AC and productivity spillovers is presented. A total of 60 articles were reviewed. Findings – The SLR revealed that human capital and R&D investments are the most frequently cited determinants of AC. R&D is especially important for developing countries. Research, Practical & Social implications – Public policies targeting R&D development may be a valuable strategy to facilitate productivity spillovers in developing countries. Originality/value – This paper analyzes the determinants of AC while verifying how both developed and developing countries can benefit from FDI, which is of great importance considering the growth of FDI in developing countries. Keywords - Foreign Direct Investment. Productivity. Spillover.